1999
DOI: 10.1103/physrevlett.83.2163
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Superelastic Electron Collisions fromH2+Studied by Dissociative Recombination Using an Ultracold Electron Beam from a Cooler Ring

Abstract: The dissociative recombination rate of H 2 1 was measured as a function of the storage time with an ultracold electron beam in a storage ring. The H 2 1 ions vibrationally relax with time, and almost reach the vibrational ground state at a time of 25 s after injection. The magnitude of the ground-state population after 25 s far exceeds that expected based on the initial ground-state population and its decay. This indicates the existence of a superelastic collision process, where electrons are scattered from ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Collisions with both residual gas molecules and electrons are known to affect the rovibrational populations in stored beams of molecular ions [47,48,49,50]. The relevant elementary reactions between the stored He intact, but changing its rovibrational excitation.…”
Section: Collisional Effects On Rovibrational Populationsmentioning
confidence: 99%
“…Collisions with both residual gas molecules and electrons are known to affect the rovibrational populations in stored beams of molecular ions [47,48,49,50]. The relevant elementary reactions between the stored He intact, but changing its rovibrational excitation.…”
Section: Collisional Effects On Rovibrational Populationsmentioning
confidence: 99%
“…Cross sections as a function of the storage time were observed for D + 2 and H + 2 ions already in early work at storage rings, including CRYRING [28,29] where significant increases of the relative population in v = 0 were found during storage times of up to ∼40 s. It was first suspected that the effect would be due to the preferential destruction of vibrationally excited ions either by collisions with rest gas molecules [28] or by the dissociative recombination process itself [29]. Later, similar measurements at TARN II [30] finally demonstrated that indeed H + 2 ions in higher vibrational states were converted into ground-state (v = 0) ions during electron cooling, giving evidence for electron-induced vibrational de-excitation ("super-elastic collisions").…”
Section: Cooling Of Internal Degrees Of Freedommentioning
confidence: 77%
“…Moreover, due to the super-elastic collisions in the electron cooler, further deexcitation of vibrationally excited states could be expected [20]. Measurements were made after 3 s and 17 s of storage.…”
Section: Resultsmentioning
confidence: 99%